Artificial Intelligence Uncovers Natural MMP Inhibitor Crocin as a Potential Treatment of Thoracic Aortic Aneurysm and Dissection - Qi, Feiran; Liu, Yan; Zhang, Kunlin; Zhang, Yanzhenzi; Xu, Ke; Zhou, Mei; Zhao, Huinan; Zhu, Shuolin; Chen, Jianxin; Li, Ping; Du, Jie (Frontiers in Cardiovascular Medicine, 2022)
Thoracic aortic aneurysm and dissection (TAAD) is a lethal cardiovascular condition without effective pharmaceutical therapy. Identifying novel drugs that target the key pathogenetic components is an urgent need. Bioinformatics analysis of pathological studies indicated “extracellular matrix organization” as the most significant functional pathway related to TAAD, in which matrix metallopeptidase (MMP) 2 and MMP9 ranked above other proteases. MMP1-14 were designated as the prototype molecules for docking against PubChem Compound Database using Surflex-Dock, and nine natural compounds were identified. Using a generic MMP activity assay and an aminopropionitrile (BAPN)-induced TAAD mouse model, we identified crocin as an effective MMP inhibitor, suppressing the occurrence and rupture of TAAD. Biolayer interferometry and AI/bioinformatics analyses indicated that crocin may inhibit MMP2 activity by direct binding. Possible binding sites were investigated by Alphafold2. Overall, the integration of artificial intelligence and functional experiments identified crocin as an MMP inhibitor with strong therapeutic potential.